84.3k views
3 votes
Simplify the expression and solve the equation. Show all calculations

Simplify the expression and solve the equation. Show all calculations-example-1

1 Answer

7 votes


\displaystyle\bf\\√(5p+5)=√(6p+3)\\\\ 5p+5=6p+3\\\\5p-6p=3-5\\\\-p=-2~\Big|*(-1)\\\\\boxed{\bf p=2}\\\\\text{Verify:}\\\\√(5*2+5)=√(6*2+3)\\\\√(10+5)=√(12+3)\\\\√(15)=√(15)~~~~OK!

.

User George Tomlinson
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.